Konstruksi Bangunan dan Ragam Hias pada Arsitektur di Kraton Yogyakarta: Kajian Eksploratif - Samedyastoety, Medy Krisnany (Jurnal TekstuReka, 2023)
The Yogyakarta Palace complex as a trace of traditional Javanese architecture is now used as a cultural tourism destination, with at least seven buildings that are open to the public. Unfortunately, there are still not many documented studies discussing these buildings, especially related to architectural construction and art detailing. From this, the author conducted an explorative study with the intention of making it easier for ordinary people and academics to recognize and understand traditional buildings in the Yogyakarta Palace complex. The method used by the author is field survey, photographing and sketching existing architectural elements (construction and decoration), scanning, and data processing with literature study.